Mechanical Evaluation of Pure Titanium Dental Implants Coated with a Mixture of Nano Titanium Oxide and Nano Hydroxyapatite - Muna Nasir; Hanan Abdul Rahman (College of Dentistry/ University of Baghdad, 2016)
Background: The type of dental implant surface is one of many factors that determine the success of implant restoration. This study aimed to study the effect of mixture of nano titanium oxide with nanohydroxyapatite coating of screw shaped CPTi dental implant on bond strength at bone implant interface by torque removal test related to two healing periods (2 and 6 weeks). Materials and methods: Dip coating process was performed to get an even coating layer on CPTi screws. X-ray diffraction (XRD) analysis and microscopical examination were performed on the coating surfaces of the CPTi. The tibia of 10 white New Zealand rabbits was chosen as implantation sites. The tibia of each rabbit received two screws, one was coated with mixture of nanoTio2and nanoHA and the other was coated with nanoHA and a total of 40 screws were implanted. Torque removal test was performed to measure bond strength between implant and bone, after 2 and 6 weeks healing periods. . Results: The results revealed, that the mean removal torque recordings for the mixture of nanoTio2and nanoHA coated screws was significantly greatly than the nanoHA covered screws over the two periods of time(2and6 weeks). There was an increase in the torque value with time. Conclusion: Commercially pure titanium implant coated with mixture of nanoTio2andnanoHApresented an increasing bond strength at bone implant interface than nanoHA , after 2 and 6 weeks (20.13±4.4 N.cm , 26.47±4 N.cm. ) in comparison to nanoHA coating after 2 and 6 weeks (15.16±2.5 N.cm , 20.12±2.3 N.cm) .